Mitomycin C Inhibits Esophageal Fibrosis by Regulating Cell Apoptosis and Autophagy via lncRNA-ATB and miR-200b - Zhang, Yin; Wang, Qinge; Xu, Yuping; Sun, Jing; Ding, Yanbo; Wang, Li; Chen, Bingfang; Sun, Kewen; Chen, Jianping (Frontiers in Molecular Biosciences, 2021)
Benign esophageal strictures (BESs) frequently results from esophageal fibrosis. The transformation of fibroblasts into fibrocyte is an important cause of fibrosis. The treatment of fibrosis is challenging. Some previous studies have indicated the antifibrotic effect of mitomycin C (MMC). However, the mechanism of action of MMC and its optimal dose for treatment remains unclear. In the present study, the role of MMC in fighting fibrosis and its mechanism was investigated. Human esophageal fibroblast cells (HEFs)were treated without or with MMC, at 2, 5, 10 μg/ml, combining with mimic lncRNA-ATB, miR-200b inhibitor, rapamycin (RAPA), and 3-Methyladenine (3-MA). The cell viability, and cell apoptosis were evaluated. In addition, expression of apoptosis related proteins (caspase8 and caspase3), autophagy related proteins (LC3II and ATG5) and fibrosis related proteins (α-SMA collagen-1 and TGF-β) were also evaluated. Furthermore, autophagosome was observed by transmission electron microscope. Results showed that the expression of lncRNA-ATB was down-regulated and miR-200b was up-regulated after treated with MMC. And MMC induced cell apoptosis and inhibited cell autophagy. On the other hand, RAPA, mimic lncRNA-ATB and miR-200b inhibitor reduced fibrogenic effect of MMC on HEFs. Collectively, this study suggests that MMC inhibited esophageal fibrosis by regulating cell apoptosis and autophagy via downregulating lncRNA-ATB and upregulating miR-200b.